ChemInform Abstract: High Performance 5 V LiNi0.5Mn1.5O4 Spinel Cathode Materials Synthesized by an Improved Solid‐State Method. Issue 52 (10th December 2015) - Gao, Zhi‐Gang; Sun, Kai; Cong, Li‐Na; Zhang, Yu‐Hang; Zhao, Qin; Wang, Rong‐Shun; Xie, Hai‐Ming; Sun, Li‐Qun; Su, Zhong‐Min
Abstract: LiNi0.5 Mn1.5 O4 is fabricated by ball milling of a stoichiometric mixture of LiOH, Ni(OAc)2, and Mn(OAc)2 (400 rpm, 20 h) followed by drying (100 °C, 10 h), calcination in either air or pure N2 (450 °C, 3 h), and finally calcination in air at 750 °C (cooling rate of 3 °C/min).